100 days of ELF/VLF generation via HF heating with HAARP. Issue 10 (3rd October 2013) - Cohen, M. B.; Gołkowski, M.
<x xml:space="preserve">Abstract</x> [1] Extremely low frequency/very low frequency (ELF/VLF) radio waves are difficult to generate with conventional antennas. Ionospheric high frequency (HF) heating facilities generate ELF/VLF waves via modulated heating of the lower ionosphere. HF heating of the ionosphere changes the lower ionospheric conductivity, which in the presence of natural currents such as the auroral electrojet creates an antenna in the sky when heating is modulated at ELF/VLF frequencies. We present a summary of nearly 100 days of ELF/VLF wave generation experiments at the 3.6 MW High Frequency Active Auroral Research Program (HAARP) facility near Gakona, Alaska, at a variety of ELF/VLF frequencies, seasons, and times of day. We present comprehensive statistics of generated ELF/VLF magnetic fields observed at a nearby site, in the 500–3500 Hz band. Transmissions with a specific HF beam configuration (3.25 MHz, vertical beam, amplitude modulation) are isolated so the data comparison is self‐consistent, across nearly 5 million individual measurements of either a tone or a piece of a frequency‐time ramp. There is a minimum in the average generation close to local midnight. It is found that generation during local nighttime is on average weaker but more highly variable, with a small number of very strong generation periods. Signal amplitudes from day to day may vary by as much as 20–30 dB. Generation strengthens by ∼5 dB during the first ∼30 min of transmission, which may be a signature of slow electron density changes from sustained HF heating. Theoretical calculations are made to relate the amplitude observed to the power injected into the waveguide and reaching 250 km. The median power generated by HAARP and injected into the waveguide is ∼0.05–0.1 W in this baseline configuration (vertical beam, 3.25 MHz, amplitude modulation) but may have generated hundreds of watts for brief durations. Several efficiency improvements have improved the ELF/VLF wave generation efficiency further.